Stochastic petri nets in the impact of the capacity in the service in mass-produced restaurants - Orejuela Cabrera, Juan Pablo (Scientia et Technica, 2018)
in the present paper, a methodology based on stochastic petri nets is proposed to measure the impact caused by the capacity constraints of productive factors on the level of service in mass-produced restaurants. The system under study is identified and a discrete simulation model based on Stochastic Petri Nets is developed, which considers the most representative components and characteristics of the system and the interrelations between them. The test is performed in a restaurant that serves more than 4,500 lunches on day, where the impact of the production and service stages can be identified and the most critical and its effects were characterized.